Facility staff perspectives on the implementation of Maternal and Perinatal Death Surveillance and Response in six health facilities in Kigoma, Tanzania - Sarah Huber-Krum; Sarah Hartley; Patricia Spencer; Lauren Galioto; Abdulaziz Msuya; Florina Serbanescu (PLoS ONE, 2026)
Background Maternal and Perinatal Death Surveillance and Response (MPDSR) is an important accountability mechanism for preventing avoidable deaths and addressing gaps in care. Health facilities in resource constrained settings often face barriers to implementing and sustaining MPDSR. The purpose of this study was to identify factors that may influence MPDSR implementation outcomes in health facilities in Tanzania. Methods Semi-structured, in-depth interviews (IDIs) were conducted in January 2024 with 17 delivery care providers (e.g., doctors, midwives, anesthesiologists) and 5 health administrators who oversaw or facilitated the facility’s MPDSR process. The implementation outcomes framework and the Practical, Robust, Implementation and Sustainability Model (PRISM) were used to guide the study, the development of interview guides, and analysis. We analyzed transcripts using a multistage approach and the constant comparative method. Results We identified several factors that may have impacted MPDSR implementation outcomes, which we grouped into three primary themes: (1) organizational and staff perspectives on MPDSR, (2) characteristics of the implementation setting, and (3) implementation and sustainability infrastructure. Subthemes included more specific barriers and facilitators that were related to MPDSR implementation outcomes. Prominent facilitators included positive perspectives of MPDSR, ongoing training and mentorship, and community engagement. Major barriers included lack of organizational readiness, resource, financial and other constraints, and blame culture. Conclusions Identifying factors that influence MPDSR implementation outcomes is important for understanding barriers and facilitators to implementation. Fostering safe environments (i.e., no blaming), addressing barriers to staff participation and motivation, and implementing monitoring systems for MPDSR recommendations may help strengthen implementation outcomes and, ultimately, sustainability.